1995
DOI: 10.1177/0022022195264006
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attributions of Underachieving Fourth-Grade Students in China, Japan, and the United States

Abstract: Discrepancy between predicted and actual achievement scores was standardized within China, Japan, and the United States; 85 of 738 fourth-grade students were identified as underachievers. An equal-sized group of students achieving in the expected range was created with a matching procedure. All subjects responded to open-ended questions addressing their beliefs about the reasons for successful and unsuccessful mathematics performance. The students' responses were categorized and analyzed according to Weiner's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…Stevenson and Lee (1990) reported that relative to Chinese and Japanese, American mothers stress their child's ability in explaining good performance at school. In a similar study, Tuss, Zimmer, and Ho (1995) found that Asian students perceive effort as a more important factor for success than American students do. The latter tend to attribute success to ability, task difficulty, and situational factors such as mood.…”
mentioning
confidence: 86%
“…Stevenson and Lee (1990) reported that relative to Chinese and Japanese, American mothers stress their child's ability in explaining good performance at school. In a similar study, Tuss, Zimmer, and Ho (1995) found that Asian students perceive effort as a more important factor for success than American students do. The latter tend to attribute success to ability, task difficulty, and situational factors such as mood.…”
mentioning
confidence: 86%
“…The central conceptual structure of number develops through two stages in early childhood. In the predimensional period, roughly at 4 years of age, children have two separate mathematical schemas: the global quantity schema that permits them to answer questions about ''more'' and ''less'', and the Whitmore, 1992;Jose, Huntsinger, Huntsinger, & Liaw, 2000;Stevenson et al, 1993;Tuss & Zimmer, 1995) have been considered as factors underlying Asian children's superior mathematical performance. However, since cross-cultural comparisons of mathematical performance have mainly focused on specific skills and particularly on children aged 6 years or above, our knowledge of the crosscultural differences in young children's combined general and specific numerical skills is limited.…”
Section: Young Children's Number Sensementioning
confidence: 99%
“…Where regression has been used elsewhere in the identification of underachievers, it has relied almost exclusively on the school performance / mental ability test discrepancy described earlier (Lau and Chan 2001, Tuss et al 1995, Whitmore 1980. Our new study used a larger number of additional variables related to academic performance (such as gender, ethnicity, poverty, motivation and prior attainment) to enhance the model and hence predict examination performance at age 14.…”
Section: 2mentioning
confidence: 99%